Two-stage strategy for neglected Monteggia fracture in children: A retrospective study of 51 patients. Issue 10 (12th March 2021) - Li, Jin; Zhao, Xiaolong; Rai, Saroj; Ding, Yuhong; Zhang, Qi; Ze, Renhao; Tang, Xin; Liu, Ruikang; Hong, Pan
Abstract : Abstract: A neglected Monteggia fracture is defined as the fracture of the proximal ulna associated with radial head dislocation (RHD) without undergoing any treatment for 4 weeks or more after injury. One-stage operation of ulnar corrective osteotomy and open reduction of RHD might result in many complications. Therefore, a two-stage strategy, including ulnar osteotomy (UO) with or without annular ligament reconstruction (ALR), was adopted at our institute since 2010. We performed a retrospective review of 51 patients with neglected Monteggia fracture between January 2010 and January 2018. Patients with bilateral problems or concomitant injuries in the ipsilateral extremity were excluded. Radiological and clinical data were collected from Hospital Database and clinical visits. All patients were divided into 2 groups based on the status of the ALR: the UO alone (UO) group and the ALR group. There were 15 patients in the UO group and 36 patients in the ALR group. The age in the UO group (6.1 ± 2.3, year) was significantly younger than the ALR group (9.8 ± 2.8, year) ( P  < .001). Concerning the duration from initial injury to surgery, there was a significant difference between the UO group (8.6 ± 3.2 months) and the ALR group (23.3 ± 12.6 months, P  < .001). Concerning the preoperative elbow function, there was no significant difference between the UO group (67.6 ± 5.0) and the ALR group (66.6 ± 4.4) according to the Mayo elbow performance score (MEPS) ( P  = .51). Concerning the postoperative parameters, including postoperative ROM of the joint, removal of external fixator (6.7 ± 0.8, 6.9 ± 0.9 weeks) ( P  = .55), lengthening (8.9 ± 2.5, 10.3 ± 2.5 mm) ( P  = .10) and MEPS (92.7 ± 2.1, 91.6 ± 2.1) ( P  = .08), there was no significant difference between the UO group and ALR group. Two-stage strategy is a reasonable choice for selected patients with long-lasting RHD with ulnar deformity.